2014
DOI: 10.1016/j.foodres.2014.01.033
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to monitor the oxidation process of different types of heated oils by using chemometric tools

Abstract: The oxidative stability of seven oils with different fatty acid profiles was assessed.Oxidation at 0, 2 and 4h at 180ºC was monitored by measuring the absorbance of thiobarbituric acid reactive substances (TBARS) along the absorption spectrum (300-600 nm), the volatile aldehydes (HS-SPME-GC-MS) and the fatty acid profile (FID-GC).TBARS absorption spectrum behavior depended on the lipid composition of heated oils.Higher absorbance increments during heating were noticed at 390 nm compared to 532 nm (from 2 to 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 26 publications
1
35
1
1
Order By: Relevance
“…This result was inconsistent with previous reports in which MUFA content also increased with the degradation of PUFA . It was reported that MUFA contents in olive oil and high‐oleic sunflower oil decreased during frying at 180 °C for 4 h, which implied that MUFA decreased only in highly monounsaturated oils and MUFA oxidation may significantly contribute to the deterioration of these oils.…”
Section: Resultscontrasting
confidence: 93%
“…This result was inconsistent with previous reports in which MUFA content also increased with the degradation of PUFA . It was reported that MUFA contents in olive oil and high‐oleic sunflower oil decreased during frying at 180 °C for 4 h, which implied that MUFA decreased only in highly monounsaturated oils and MUFA oxidation may significantly contribute to the deterioration of these oils.…”
Section: Resultscontrasting
confidence: 93%
“…In this study, E,E -2,4-heptadienal r:0.92 and 2-propenal r:0.88 with PCA1 were used as the quality markers of oxidation of the n-3 PUFA oil in the Rancimat test. In another report, E,E -2,4-heptadienal is important and is a high concentration volatile compound of the oxidation of n-3 PUFA oil 34,36 . In this study, E,E -2,4-heptadienal has a high correlation and a high concentration during oxidation of the n-3 PUFA oil.…”
Section: Chemometric Analysis Pca and Ahcmentioning
confidence: 98%
“…Hexanal was a quality markers for the oxidation of the oil, but it does not oxidize the n-3 PUFA oil in the Rancimat test. However, the oxidative properties of various oil were not distinguished from each other by taking only a single compound into account 33,34 . Aldehydes are common volatile compounds in oil that are produced as a result of the oxidation process.…”
Section: Chemometric Analysis Pca and Ahcmentioning
confidence: 99%
“…Lipid oxidation is a serious problem pertaining to many food products. One group of reactions is essentially oxidation of unsaturated fatty acid chains, typically via the addition of oxygen across the double bonds of unsaturated fatty acids to form hydroperoxides, which decompose to form secondary oxidation products (Poyato and others ). This reaction is normally called autoxidation, which can occur at room temperature and proceeds by a free radical mechanism; the reaction is catalyzed by light in the presence of enzymes or metal ions (Nawar ).…”
Section: Introductionmentioning
confidence: 99%